KAJIAN MACAM TIGA JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN OKRA MERAH (Abelmoschus esculentus L. moench): KAJIAN MACAM TIGA JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN OKRA MERAH (Abelmoschus esculentus L. moench) - Siswadi Siswadi; Saiful Bahri; Ayu Rosiani Rosiani (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
The ititle iof iresearch iis ithe iresearch ito ithe ianalyze iof iThree iTypes iof iManure ion ithe iGrowth iand iYield iof iRed iOkra i(Abelmoschus iesculentus iL. iMoench). iThis istudy iaims ito ianalyze ithe ieffect iof imanure ion ithe igrowth iand iyield iof ired iokra i(Abelmoschus iesculentus iL. iMoench) iwhich iwas icarried iout ifrom iSeptember i-November i2021. iThe istudy iwas icarried iout iin iBunder iHamlet, iKedungwaduk iVillage, iKarangmalang iDistrict, iSragen iRegency. iWith ian ialtitude iof i84-190 imeters iabove isea ilevel. iThe itype iof isoil iused iis iRegosol isoil. iThis istudy iused ia icompletely irandomized idesign i(CRD) isingle ifactor ias ifor ithe itypes iof itreatment, inamely: iA i(without ifertilizer), iB i(giving icow imanure i125 ig/tan), iC i(giving igoat imanure i125 ig/tan), iD i(giving ichicken imanure i125 ig/tan), iE i(applying icow, igoat, ichicken imanure i125 ig/tan), iF i(giving icow iand igoat imanure i125 ig/tan), iG i(giving icow iand ichicken imanure i125 ig/plant) itan), iH i(giving igoat iand ichicken imanure i125 ig/tan). iThe itreatment iconsisted iof i8 itypes iof itreatment iwhich iwere irepeated i4 itimes iso ithat i32 iexperimental iunits iwere iobtained. iData iwere ianalyzed iby iDuncan itest iat i5% ilevel. iParameters iobserved iincluded iplant iheight, inumber iof ileaves, iweight iof iwet istover, iweight iof idry istover, inumber iof ifruit iper iplant, iweight iof iplant ifruit. iThe iresults ishowed ithat ithe idose itreatment iof ithree itypes iof imanure ion ithe igrowth iand iyield iof ired iokra iplants idid inot isignificantly iaffect iplant, inumber iof ileaves, ifruit iweight, inumber iof ifruit, iweight iof iwet istover iand iweight iof idry istover.